A history of modern drama. - Krasner, David, 1952- (Wiley-Blackwell, 2012)
"Covering the period 1879 to 1959, and taking in everything from Ibsen to Beckett, this book is volume one of a two-part comprehensive examination of the plays, dramatists, and movements that comprise modern world drama. Contains detailed analysis of plays and playwrights, connecting themes and offering original interpretations Includes coverage of non-English works and traditions to create a global view of modern drama Considers the influence of modernism in art, music, literature, architecture, society, and politics on the formation of modern dramatic literature Takes an interpretative and analytical approach to modern dramatic texts rather than focusing on production history Includes coverage of the ways in which staging practices, design concepts, and acting styles informed the construction of the dramas"--